2003
DOI: 10.1021/jm030090t
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Cytotoxic Properties of Trichoverroids and Their Macrolide Analogues Produced by Saltwater Culture of Myrothecium verrucaria

Abstract: Saltwater culture of Myrothecium verrucaria, separated from a Spongia sp. collected in Hawaii, was a source of three new trichothecenes, 3-hydroxyroridin E (1a), 13′-acetyltrichoverrin B (2), and miophytocen C (3) and nine known related compounds (1b, 4, 5, 6, 7a, 7b, 8, 9a, and 9b). The stereostructures of the new compounds were established on the basis of 1D and 2D NMR spectral analyses and a chemical transformation. At the same time, the stereostructures of known compounds, 1b, 4, and 5 reported previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 38 publications
1
66
0
Order By: Relevance
“…This observation suggested that it was most likely a trichothecene compound belonging to the macrocyclic 10,13-cyclotrichothecane group. [1,13] This assumption was subsequently confirmed by a set of 2 D NMR spectroscopic experiments ( 1 H-1 H COSY, NOESY, HMQC, and HMBC spectra) that provided data for the unequivocal assignment of all 1 H and 13 C NMR spectral data (Tables 1 and 2). In the 1 H-1 H COSY spectrum of 1, the coupling sequences from H-2 through H-4, between H-7 and H-8, and of H-10 with H-11 and H-13 were readily recognized and connected to the sesquiterpenol moiety according to the HMBC correlations of (1) H-2 with C-4, C-5, and C-11, (2) H-3a with C-5 and C-12, (3) H-4 with C-5, C-6, and C-12, (4) H-11 with C-9 and C-15, and (5) H-15 with C-1', C-7, and C-11.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…This observation suggested that it was most likely a trichothecene compound belonging to the macrocyclic 10,13-cyclotrichothecane group. [1,13] This assumption was subsequently confirmed by a set of 2 D NMR spectroscopic experiments ( 1 H-1 H COSY, NOESY, HMQC, and HMBC spectra) that provided data for the unequivocal assignment of all 1 H and 13 C NMR spectral data (Tables 1 and 2). In the 1 H-1 H COSY spectrum of 1, the coupling sequences from H-2 through H-4, between H-7 and H-8, and of H-10 with H-11 and H-13 were readily recognized and connected to the sesquiterpenol moiety according to the HMBC correlations of (1) H-2 with C-4, C-5, and C-11, (2) H-3a with C-5 and C-12, (3) H-4 with C-5, C-6, and C-12, (4) H-11 with C-9 and C-15, and (5) H-15 with C-1', C-7, and C-11.…”
Section: Resultsmentioning
confidence: 84%
“…Among this type of secondary metabolite, a number have been demonstrated to play a substantial role in cancer prevention, [1] immunomodulation, [2] plant tissue induction, [3] phytotoxicity, [4] fungus suppression, [5] malaria management, [6] biocontrol agent, [7] and mammalian intoxications. [8] Renewed understanding of the relevant molecular mechanisms of action of these compounds highlighted that the biochemical processes, in most cases, were fascinatingly unique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…107 Another cyclotrichothecane derivative miophytocen C 132, together with 3-hydroxyroridin E and 13 -acetyltrichoverrin B, were isolated from a saltwater culture of Myrothecium verrucaria, separated from a Spongia sp., collected in Hawaii. 108 GC-MS techniques have been used in the analysis of trichothecene mycotoxins in commercial corn harvested in Brazil. 109 The synthesis of four mycotoxins of this type labelled with carbon-13 and their application as internal standards in stable isotope dilution assays for their determination in foods has been described.…”
Section: Bicyclofarnesanementioning
confidence: 99%
“…Other compounds: Several other anticancerous compounds apart from the above mentioned categories includes steroid, diketopiperazine, terpenes, trichoverroids and peptides. Myrothecium verrucaria derived trichoverroid compounds such as 3-hydroxyroridin E, 13' acetyltrichoverrin B and miophytocen C shows significant cytotoxicity against murine and human tumor cell lines 26 . Aragusterol C, novel chlorinated steroid, was isolated from an Okinawan marine sponge of the genus Xestospongia.…”
Section: Fatty Acidsmentioning
confidence: 99%